Political Trust Influences the Relationship Between Income and Life Satisfaction in Europe: Differential Associations With Trust at National, Community, and Individual Level - Clench-Aas, Jocelyne; Holte, Arne (Frontiers in Public Health, 2021)
Background: A high level of well-being is associated with personal, community and national income, as well as personal, social and political trust. How these measures relate to each other within and between countries and within and across structural levels of society is largely unknown. To study this, we propose a three-layer nested socio-structural model. Each layer (individual, community, country) contains a measure of income, trust and satisfaction. Method: With this model, we analyzed data from two waves of the European Social Survey (ESS, 2006, 2012) in 19 countries (N = 72,461; weighted N = 73,307) with multilevel techniques. Indicators were personal, community, and national income; personal, social and political trust; and personal life satisfaction, social and political satisfaction. Results: Personal life satisfaction was associated with all income and trust variables. Greatest effect on personal life satisfaction, came from the national level, including political trust and income. However, 2/3 of the variance in personal life satisfaction came from income, that is personal, community and national. Within each socio-structural level, satisfaction was associated with income, but significantly modified by trust. When income and trust at all three levels were included, there was a significant association of the national layer on the social layer, and of the social layer on the individual layer as to the income–personal life satisfaction relationship. Consistent with the “the buffer hypothesis,” all three forms of trust acted as a buffer against the effect of personal income on life satisfaction. Low-trust countries had strong income–personal life satisfaction associations and the moderating role of trust was also stronger. High- and medium-trust countries had no such associations. Likewise, direct associations between political and personal trust were much stronger in the low-trust countries. Conclusion: The model presented in this study provides authorities with a framework for policies that will improve the general well-being of their population. Trust and income strongly influence personal life satisfaction. Money is the most important. However, trust forcefully dampens the effect of income. Politicians who want to enhance their population's personal life satisfaction, should raise the levels of trust in their electorate.